Electrochemical deposition of Ag2Se nanostructures. (February 2017) - Genovese, Luigi; Cocchiara, Cristina; Piazza, Salvatore; Sunseri, Carmelo; Inguanta, Rosalinda
Graphical abstract: Highlights: Ag2 Se nanostructures were obtained by electrodeposition in polycarbonate template. Aqueous solution was used with and without thiocyanate. Morphology, structure, and composition change with bath composition and H2 evolution reaction. On Cu support compact, uniformly distributed, and mechanically firm nanowires were formed. On Ni support, nanotubes were preferentially formed due to H2 evolution. Abstract: AgSe based nanostructures (nanowires or nanotubes) were obtained by electrodeposition. A systematic investigation was carried out, varying concentration of the precursors, pH of the electrolytic solution, ligands, and deposition mode, to study the effect of all these parameters on the growth of nanostructures. Nanostructure morphology depends also on the type of metal that was used as support, due to the secondary reaction of hydrogen evolution. On Ni support, the H2 evolution reaction led to formation of only nanotubes, while on copper substrate also nanowires were obtained. Composition of nanostructures depends strongly on solution pH. X-ray diffraction and Raman spectroscopy showed that in thiocyanate-free bath nanostructures consist in orthorhombic Ag2 Se and metallic Ag. At higher pH values, the metallic Ag phase increased and the co-deposition of Se also occurred. We also found that the use of a thiocyanate bath with a specific composition permits to obtain nanostructures of pure orthorhombic Ag2 Se.